Tameness of the pseudovariety LS1 - Costa, José Carlos (2004)
The notion of k-tameness of a pseudovariety was introduced by Almeida and Steinberg and is a strong property which implies decidability of pseudovarieties. In this paper we prove that the pseudovariety LSl, of local semilattices, is k-tame.